IMPROVED CROSSHOLE RADAR TOMOGRAPHY BY USING DIRECT AND REFLECTED ARRIVAL TIMES - Tronicke J.; Tweeton D.R.; Dietrich P.; Appel E. (My University, 2001)
Traveltime tomography by inverting direct arrival times is the most common technique in crosshole radar surveying. In a standard crosshole experiment, the inversion is a mathematically nonunique process due to the limited range of viewing angles producing ambiguous and smeared results. If possible, additional information should be extracted from the data or added from the outside to improve and constrain the inversion and the interpretation. In low attenuation media, reflected wave energy can also be present in the crosshole data. Reflections are often caused by well-known interfaces, such as the free earth surface or the groundwater table. Because of their differing travel paths, these reflected events contain additional information about subsurface structure and parameter distribution. We present a technique to include reflection traveltimes associated with known interfaces into tomographic traveltime inversion of crosshole radar data. If in a crosshole radar survey such reflections can be clearly identified, the total number of rays and the range of raypath angles are increased by the presented inversion strategy. Applications to a synthetic and a real field data set show the practicability and the improvements offered by this method. The results show that horizontal smearing is reduced and local anomalies are better contoured compared to standard crosshole tomography using only direct arrivals.
Keywords: BOREHOLE RADAR; INVERSE PROBLEMS; TOMOGRAPHY; REFLECTION WAVES